A cross-sectional study on ante-natal depression in a tertiary health care hospital in Navi Mumbai - Joshi, Sumedha M.; Ravi, Shilpa; Velankar, Deepa H. (International Journal Of Community Medicine And Public Health, 2020)
Background: Depression is a common source of disability among women. Antenatal depression has been often overlooked and under diagnosed, throughout the world especially in the developing countries like India. This study was conducted to assess the mental health status of pregnant women attending the antenatal clinic in a tertiary health care hospital. Methods: A cross-sectional study was conducted over a period of three months among randomly selected pregnant women attending the antenatal clinic of a tertiary hospital. A total of 170 pregnant women formed the study subject. Data was collected using a pre-designed, pre-tested, semi-structured questionnaire and analysis was done using SPSS version 20.0. Results: Among the study population, the prevalence of depression was found to be 20.6%. Depression was significantly associated with the socio-economic status and education of the study subjects. Women with family discord were significantly more depressed than those with no discord. Unplanned pregnancy and preference of male child very significant factors for depression. Multiparity and bad obstetric history also showed a higher level of depression which was statistically significant. Conclusions: There is a significant prevalence of antenatal depression which needs screening and appropriate management. Maternal health policies must integrate maternal depression as a disorder of Public Health importance and interventions should target the pregnant women as early as possible.